PENGARUH CORPORATE REBRANDING TERHADAP LOYALITAS NASABAH BNI DENPASAR MELALUI BRAND ASSOCIATIONS, KEPUASAN, DAN REPUTASI PERUSAHAAN - Ni Putu Sri Mulyani (Jurnal Manajemen dan Bisnis, 2013)
The research was an explanatory by means of cross sectional method.Comprehensively, the objective of this research was to prove and analyze the effect of :corporate rebranding to customers’ loyalty, corporate rebranding to brand associations,corporate rebranding to customers’ satisfaction, corporate rebranding to corporatereputation, brand associations to customers’ satisfaction, brand associations to customers’loyalty, customers’ satisfaction to corporate reputation, customers’ satisfaction to customers’loyalty.This research using 130 respondents taken by systematic random sampling withproportional allocation. The instrument used were questionnaires. The technique ofanalyzing data was Structural Equation Modelling or SEM by means of AMOS PackageProgram, version 18.0.Keywords: corporate rebranding, brand associations, satisfaction, corporate reputation, loyalty.